Hazardous waste management - LaGrega, Michael D. (McGraw-Hill, 1994)
The book is divided into four major parts. Part I provides background material for a complete understanding of hazardous wastes. Part II examines the methods currently used by management in industry to understand the gnitude of hazardous waste problems and how to avoid many of the problems of the past. Part II contains a selection of treatment and disposal methods. Part IV covers site remediation. Tjis includes the characterization of a site, the assessment of risks that it poses, and development and selection of remedies